(untitled) (Marketing Journal, 2025)
This article describes the scientific and theoretical aspects of using the discounted cash flow method in assessing the capital value of a joint stock company. Also, the discounted cash flows method was used to assess the capital value of JSC "KOKAND MECHA NICAL PLANT". It also identifies existing problems in using the method of discounted cash flows in the assessment of the capital value of the joint -stock company and ways to overcome them.